Localization of Newcastle Disease Virus (Ndv-Af2240) in 4T1 Xenotransplant Breast Cancer Balb/C Mice - Motalleb, Gholamreza (2009)
In situ reverse transcriptase polymerase chain reaction (in situ RT-PCR), polyclonal chicken antibody and goat anti-chicken antibody conjugated with fluorescein isothiocynate (FITC) using confocal laser scanning microscopy (CLSM) and negative staining transmission electron microscopy (NSTEM) were carried out to detect the NDV-AF2240 in tumor, liver, brain and lung during intratumural injection in 4T1 xenotransplant breast tumor in female BALB/c mice. A total of 300 female BALB/c mice were divided randomly into 15 groups (5 non cancerous groups, 10 cancerous groups) consisting 20 mice per group. The normal control (NC), normal treated with 8, 16, 32 and 64HA units of NDV-AF2240 respectively named as N/NDV8, N/NDV16, N/NDV32 and N/NDV64. The mice in cancerous groups were initially inoculated sub-cutaneously with 4T1 cells; co-culture either with NDV AF2240 or/and tamoxifen. Cancerous groups were divided into cancer control (CC), cancer treated with only 5 μg/ml tamoxifen citrate (CT), cancer treated with 8, 16, 32 and 64HA units of NDV-AF2240 without tamoxifen respectively named C/NDV8, C/NDV16, C/NDV32, C/NDV64, cancer treated with 8, 16, 32 and 64HA units of NDV-AF2240 with tamoxifen respectively named as CT/NDV8, CT/NDV16, CT/NDV32 and CT/NDV64 daily for four weeks. The normal mice treated with 8, 16, 32 and 64 HA unit of NDVAF2240 did not affect its lifespan. All of the cancerous and non cancerous mice survived well and completed the 4-weeks treatment. Only 4 groups of mice developed tumor that was CC, CT, CT/CNDV32 and CT/NDV64, however these groups survived until end of the 4 weeks of treatment. Significant difference (p < 0.05) in mean body weight was found between N/NDV16, N/NDV64 and NC. Whereas, for the cancerous groups, mean body weight of the mice in CC group were significantly different (p<0.05) to compare with C/NDV8, C/NDV32, CT/NDV16, CT/NDV32 and CT/NDV64 groups. The mean tumour volume and mass of CT/NDV32 and CT/NDV64 were not significantly different (p> 0.05) to compare with each other and cancer control (CC), however, there was significant difference (p <.05) in the changes of tumour volume and mass over time. The CC and CT groups had a significantly (p<0.05) higher lung weight compared with the other groups. The CC group had a significantly (p<0.05) higher of liver weight compared with all groups. There was no significant (p>0.05) different in the brain weight between CC and all cancerous groups. To localize HN gene expression of NDV-AFF2240 in tissues, in situ RT-PCR was applied on formalin fixed paraffin-embedded (FFPE) sections that were positive by negative staining transmission electron microscopy. The HN gene expression was detected in all the breast tumor cells. However, it was found mainly in the blood vessels of the brain, liver and lung. The intensity of the HN gene expression in all the organs within the same group is significantly similar except the breast tumor tissue. There was no significant different (p>0.05) in HN gene intensity between CT/NDV8 and CT/NDV16 groups, however, it was significantly different (p<0.05) compared to CT/NDV32 and CT/NDV64 groups. Virus dissemination seems to be determined by the infusion dose during intratumoral injection. β actin as internal control was expressed in breast cancer tissue, brain, lung and liver. In situ RT-PCR showed similar constant strong intensity of β actin gene expression in all mentioned tissues. Immunofluoresence and CLSM successfully detected the virus particles in tumor and all the organs of the cancerous groups during intratumoral injection. In tumor tissue the virus are found in the cells, whereas, in the lung, brain and liver are found mainly in the blood vessels. They are mainly found at the central vein (C.V.) and sinusoidal capillaries of the liver. This phenomenon was similar to results of in situ RT-PCR. Negative staining with transmission electron microscopy as a gold standard method was successfully used to detect the NDV-AF2240 at breast tumor, lung, liver and brain tissues during intratumoral injection in 4T1 xenotransplant breast cancer induced in mice. The results illustrated the presence of NDV-AF2240 in all organs of cancerous groups, but not in the normal groups treated with virus. The morphology of Newcastle disease virus was seen pleomorphic, spherical and ranging from 60-320 nm. The virion has an envelope and prominent surface projections. Occassionally, virions were seen to be rod in shape. Besides observing the whole virus, nucleocapsids which is confined in the virion was frequently detected outside the virion and are also seen filamentous. The findings of this study showed that NDV-AF2240 suppressed the growth of breast cancer and it is disseminated in blood vessels of the brain, lung and liver, however, found in the cells of the breast cancer